2023
DOI: 10.3390/agriengineering5010015
|View full text |Cite
|
Sign up to set email alerts
|

A Full Assistance System (FAS) for the Safe Use of the Tractor’s Foldable Rollover Protective Structure (FROPS)

Abstract: The use of agricultural tractors is a major concern in agriculture safety due to the high level of risk of loss of stability combined with the frequent absence of passive safety devices such as rollover protective structures (ROPSs). Indeed, although in most cases the ROPS is installed, when working in vineyards, orchards, or in other cases of limited crop height, the tractor is usually equipped with a foldable ROPS (FROPS), which is often misused because the effort needed for raising/lowering is excessive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…These conventional devices have been studied for performance improvement and utilization [12][13][14][15][16]. Conventional safety devices play an important role in protecting the driver, but their shape and installation method can lead to the risk of rollover accidents [17,18]. Ayers et al [19] found that the risk of a continuous rollover accident increased as the center of gravity (CoG) of the tractor increased in height.…”
Section: Introductionmentioning
confidence: 99%
“…These conventional devices have been studied for performance improvement and utilization [12][13][14][15][16]. Conventional safety devices play an important role in protecting the driver, but their shape and installation method can lead to the risk of rollover accidents [17,18]. Ayers et al [19] found that the risk of a continuous rollover accident increased as the center of gravity (CoG) of the tractor increased in height.…”
Section: Introductionmentioning
confidence: 99%